2019
DOI: 10.3171/2018.5.spine171232
|View full text |Cite
|
Sign up to set email alerts
|

Cervical mismatch: the normative value of T1 slope minus cervical lordosis and its ability to predict ideal cervical lordosis

Abstract: OBJECTIVENumerous studies have attempted to delineate the normative value for T1S−CL (T1 slope minus cervical lordosis) as a marker for both cervical deformity and a goal for correction similar to how PI-LL (pelvic incidence–lumbar lordosis) mismatch informs decision making in thoracolumbar adult spinal deformity (ASD). The goal of this study was to define the relationship between T1 slope (T1S) and cervical lordosis (CL).METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 24 publications
0
60
0
1
Order By: Relevance
“…The T1 slope is the only value that links both the cervical and thoracic spine. It shows a close correlation with thoracic kyphosis, TIA, and C2-7 SVA [26] . C2-7SVA is believed to be another important indicator of cervical sagittal balance [20,21] .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The T1 slope is the only value that links both the cervical and thoracic spine. It shows a close correlation with thoracic kyphosis, TIA, and C2-7 SVA [26] . C2-7SVA is believed to be another important indicator of cervical sagittal balance [20,21] .…”
Section: Discussionmentioning
confidence: 64%
“…Staub et al reviewed the relationship between T1 slope and cervical lordosis in 103 adult patients with spinal deformity. They found that the T1 slope minus cervical lordosis ranging from 14.5° to 26.5° could maintain the horizontal balance [26] . For this reason, C2-7 SVA should be within the normal range if cervical lordosis is high or the T1 slope is low.…”
Section: Discussionmentioning
confidence: 99%
“…The T1 slope has been the only value linking both the cervical and thoracic spine. It has closely correlation with thoracic kyphosis, TIA and C2-7 SVA [26] . A higher thoracic kyphosis often results in a higher T1 slope [21] ..…”
Section: Discussionmentioning
confidence: 77%
“…Then, it implied that the T1 slope minus cervical lordosis ranged form 14.5°to 26.5°could maintain the horizontal balance. [26] . In our study, the multivariate logistic regression analysis showed T1 slope was the risk factor of ANP.…”
Section: Discussionmentioning
confidence: 99%
“…The reasonable range of C2-C7 SVA of 29.2 mm corresponded to T1S-CL of 20.7° is narrower than posterior cervical fusion reported by Hyun et al, which emphasizes the different threshold in various approaches. Staub et al [26] implied normative CL can be predicted via T1S-CL= 16.5° ± 2° based on 103 patients with cervical spine deformity. It is considered that there were differences between anterior and posterior approach on surgical-indications, internal-xtions, posterior muscle striping and preservation of ligament complex, where the solid xtion by lateral mass screw and bowstring effect from posterior muscle requires wider range of T1SCL [5,27].…”
Section: Discussionmentioning
confidence: 99%